Radical radiotherapy in epidermoid cancer in the orbitary region: ideal scheme of hypo-fractionation in times of COVID-19: a case report - Romero, Ruben A. Lara; Jimenez, Karilu Muñoz; Puch, Amelia E-Sarricolea; Lopez, Fernando H. Castillo (International Journal of Research in Medical Sciences, 2020)
There are adverse events in the patient’s environment that impact on therapeutic decisions and become a medical challenge, as is currently the management of cancer patients with radiotherapy, particularly the elderly in times of a COVID-19 pandemic, due the high risk of infection and fatal complications from non-cancer causes. Here we present the case of an 84-year-old woman with voluminous squamous cell cancer in the left orbital region, which caused intense pain, stench, and persistent bleeding. And due to persistence and time, it impacted with deterioration in the patient’s quality of life. In the end, of hypo fractionated radiotherapy management as the only modality, it evolves with a complete clinical response and total palliation of initial symptoms. The reasons for the decision to manage radiotherapy and the excellent clinical results that reinforce the idea of personalized medicine and the importance of evaluating the biopsychosocial environment of the cancer patient will be discussed.